The relationship between field tests of anaerobic power and 10-km run performance - Sinnett, A. M.; Berg, K.; Latin, R. W.; Noble, J. M. (The Journal of Strength and Conditioning Research, 2001)
The purpose of this study was to investigate the relationship between several field tests of anaerobic power and distance running performance. Thirty-six trained runners (20 men and 16 women; mean ± SD age, 27.9 ± 5.7 years) participated in this study. Tests of anaerobic power consisted of a 50-m sprint, vertical jumps from a static take-off position and with a countermovement, a plyometric leap test, and a 300-m sprint. The results indicated that gender, height, weight, percent body fat, 50-m sprint time, the height and power of both types of vertical jumps, plyometric leap distance, and the 300-m sprint time were significantly correlated with 10-km run time (p 0.05) in the total subject pool (N = 36). Stepwise multiple regression identified the plyometric leap distance to explain 73.9% of the variance in run time. When combined with 300-m sprint time, 77.9% of the variance (standard error of the estimate, 2.92 minutes) was explained. The regression equation developed is Y (10-km time) = 57.22 5.15(plyometric leap distance in meters) + 0.27(300-m sprint time in seconds). The results indicate that anaerobic power is significantly related to distance running performance and may explain a meaningful percentage of variability in 10-km run time. Therefore, it may be beneficial for distance runners to supplement aerobic training with some power and speed development such as plyometrics and sprinting.